Audience Attitudes Towards the Impact of Interactive Design on the Success of Digital Campaigns: Field Study (The International Journal for Scientific Research, 2024)
In the era of modern digital technology, digital campaigns have become an essential tool for communicating with the audience and achieving marketing and advertising goals. Digital campaigns are one of the most important means that marketers use to interact with the target audience and increase awareness and engagement with the brand or product. With the increasing importance of digital campaigns, interactive design is considered one of the main factors that affect the success of these campaigns.This study aims to identify the impact of using interactive design in advertisements on the success of digital advertising campaigns. It also aims to conduct a field study to identify the impact of the interactive design of Saudi Telecom companies’ advertisements (study sample) on the success of digital campaigns, from the perspective of the public in the eastern, western and central regions, who benefit from the services provided by these companies.
Keywords: Digital Campaigns; Interactive Design; Audience Trends; Digital Media